Smartphones to Learn English: The Use of Android Applications by Non-English Major Students in West Aceh - Hidayati, Tuti; Endayani, Thayyibatul (SCAD Independent, 2019)
Smartphones multi-functionality and practicality features are very promising in helping students to learn English language. Numerous applications related to English enables the students to be exposed to English and learn independently and conveniently outside the classroom. This study explored students own use of android applications to help them in learning English. Specifically, it investigated the types of apps the students use, examined their motives in using the apps, and figured out how the apps were perceived to help in acquiring English. The study was conducted as a qualitative study involving 15 non-English majors students recruited from three different campuses in West Aceh. The data were collected through personal interview and focus group discussion that were transcribed and analyzed by coding and concluding the information into a number of themes. It was found that the students had used a number of android apps, particularly dual language dictionary apps to support their informal English language learning. The apps were considered very helpful as the students could access vocabulary and be exposed to English frequently. Easy access and practical use of apps were perceived as the major advantages benefiting the students in gaining vocabulary and other English learning materials to develop their English language skills.